Nanofiber film assembly and method of formation
The method of using a soluble layer to detach nano fiber structures from a base layer and float them on a solvent surface addresses the handling challenges of nano fibers, ensuring their integrity and enabling their effective integration into industrial products.
Patent Information
- Application Number
- JP2022523503
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-22
- Filing Date
- 2020-10-23
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2040-10-23
AI Technical Summary
The integration of nano fibers into industrial products is challenging due to their delicate nature and dimensions, leading to issues such as tearing, breaking, or damage during processing, especially when handling nano fiber sheets and films.
A method involving a nano fiber structure assembly with a base layer and a soluble layer, where the soluble layer is dissolved to peel off the nano fiber structure from the base layer, allowing it to float on a solvent surface, facilitating handling and transfer without damage.
This method enables the handling of nano fiber structures with mechanical precision, maintaining their integrity and purity, enabling large-scale and controlled use of nano fibers in industrial applications.
Smart Images

Figure 0007623368000001 
Figure 0007623368000002 
Figure 0007623368000003
Abstract
Description
[Technical field]
[0001] Related Applications This application claims priority under 35 U.S.C. §119(e) to U.S. Provisional Patent Application No. 62 / 925,533, filed October 24, 2019, and entitled "PROCESS FOR NANOFIBER FILTRATION FILMS AND WATER-SOLUBLE GRIDS," and U.S. Provisional Patent Application No. 62 / 993,030, filed March 22, 2020, and entitled "PROCESS FOR NANOFIBER FILTRATION FILMS AND WATER-SOLUBLE GRIDS," each of which is incorporated herein by reference in its entirety.
[0002] FIELD OF THE DISCLOSURE This disclosure relates generally to nanofibers. In particular, this disclosure relates to nanofiber filtration films and the treatment of soluble substrates. [Background technology]
[0003] Nanofibers are known to have unique mechanical, optical, and electronic properties. However, due to their nanoscale dimensions, it has been difficult to devise nanofiber configurations that can be integrated into industrial products. One example of progress in the development of industrially useful embodiments of nanofibers is the production of nanofiber "forests." The forest is an array of parallel nanofibers grown perpendicular to the substrate surface. The forest can be pulled from the substrate to obtain a nanofiber sheet in which the nanofibers are parallel to each other and in the plane of the sheet. The nanofiber sheet can then be optionally formed into nanofiber yarns. Alternatively, the nanofibers can be suspended in a solvent and then applied to a filter. When the solvent is removed through a filter that is permeable to the solvent, a film of randomly oriented nanofibers remains on one side of the filter that is impermeable to the nanofibers. Summary of the Invention
[0004] In a first example, the method includes: Preparing a nanofiber structure on a substrate assembly comprising a substrate layer and a soluble layer; dissolving the soluble layer with a solvent; In response to the dissolving, floating the nanofiber structure on a surface of the solvent; peeling the nanofiber structure from the base layer while the nanofiber structure is immersed in the solvent; Includes.
[0005] Example 2 includes the subject matter of Example 1, further including removing the floating nanofiber structures from the surface of the solvent.
[0006] Example 3 includes the subject matter of Example 1, where the soluble phase is sodium chloride and the solvent is water.
[0007] Example 4 includes the subject matter of Example 1, wherein the soluble layer is a polymer and the solvent is an organic solvent.
[0008] Example 5 includes the subject matter of Example 1, further including cutting said nanofiber structure with an infrared laser prior to said fusing.
[0009] Example 6 includes the subject matter of Example 1, wherein the substrate layer includes one or more of glass, silica, silicon, polymer, and steel.
[0010] Example 7 includes the subject matter of Example 1, wherein the thickness of the soluble layer is between 10 μm and 200 μm.
[0011] Example 8 includes the subject matter of Example 2, wherein said removing includes removing the floating nanofibrous structures from the surface of the solvent using a final substrate.
[0012] Example 9 includes the subject matter of Example 1, wherein the nanofiber structure comprises at least two carbon nanofiber layers.
[0013] Example 10 includes the subject matter of Example 9, wherein each of the carbon nanofiber layers comprises at least one of a carbon nanofiber sheet, a carbon nanofiber filtration film, and a carbon nanofiber grid.
[0014] Example 11 includes the subject matter of Example 10, and further includes suspending the nanofiber structure on the surface of the solvent following complete peeling from the substrate layer.
[0015] Example 12 includes the subject matter of Example 2, wherein the removing includes using a frame to lift the floating nanofibrous structures above the surface of the solvent.
[0016] Example 13 includes the subject matter of Example 12, where the frame is a wire frame with an open central portion.
[0017] Example 14 comprises a transparent conductive film comprising a nanofiber structure on a substrate assembly, and the substrate assembly comprising a substrate layer and a dissolvable layer; The nanofiber structure is configured to float on the surface of a solvent; and The dissolvable layer is a device configured to dissolve the nanofiber structures from the substrate layer by suspending them on the surface of the solvent.
[0018] Example 15 includes the subject matter of Example 14, wherein the transparent conductive film has an electrical resistance of less than 1 Ω / sq.
[0019] Example 16 includes the subject matter of Example 14, wherein the transparent conductive film is transparent to greater than 99% of visible light.
[0020] Example 17 includes the subject matter of Example 14, wherein the soluble layer includes at least one of sodium chloride, calcium chloride, potassium bromide, starch, polystyrene, and toluene.
[0021] Example 18 includes the subject matter of Example 14, wherein the transparent conductive film is configured to be cut using at least one of a laser beam and an electrical discharge device without causing damage to the fusible layer.
[0022] Example 19 includes the subject matter of Example 14, wherein the nanofiber structure comprises at least two carbon nanofiber layers.
[0023] Example 20 includes the subject matter of Example 19, wherein each of the carbon nanofiber layers comprises at least one of a carbon nanofiber sheet, a carbon nanofiber filtration film, and a carbon nanofiber grid. [Brief description of the drawings]
[0024] [Figure 1] 1 is a micrograph of an exemplary forest of nanofibers on a substrate, according to one embodiment. [Diagram 2] FIG. 2 is a schematic diagram of an exemplary reactor for growing nanofibers, according to one embodiment. [Diagram 3] FIG. 2 is a diagram of a nanofiber sheet in one embodiment, illustrating the relative dimensions of the sheet and showing, in a schematic diagram, the nanofibers within the sheet aligned end-to-end in a plane parallel to the surface of the sheet. [Figure 4] FIG. 2 is an image of a nanofiber sheet being pulled laterally from a nanofiber forest, in one embodiment, where the nanofibers are arranged in a schematic end-to-end arrangement. [Diagram 5] FIG. 1 is a schematic diagram of a portion of a filtration nanofiber film comprising larger and longer multi-walled carbon nanofibers intermixed with single-walled and / or few-walled carbon nanofibers, in one embodiment, where all of the carbon nanofibers are randomly oriented within the plane of the film. [Figure 6]1 is an electron microscope image of a filtration film comprising a mixture of multi-walled nanotubes and few-walled and / or single-walled nanotubes, according to one embodiment. [Figure 7] 1A, 1B, and 1C show an exemplary process by which the nanofiber filtration film can be removed from the filter by insertion into water, in one embodiment. [Figure 8A] FIG. 1 illustrates the steps of an exemplary process for transferring nanofiber structures, including one or more of a nanofiber sheet, a nanofiber filtration film, a nanofiber grid, and combinations thereof, between substrates using a substrate assembly having a water-soluble layer in one embodiment. [Figure 8B] FIG. 1 illustrates the steps of an exemplary process for transferring nanofiber structures, including one or more of a nanofiber sheet, a nanofiber filtration film, a nanofiber grid, and combinations thereof, between substrates using a substrate assembly having a water-soluble layer in one embodiment. [Figure 8C] FIG. 1 illustrates the steps of an exemplary process for transferring nanofiber structures, including one or more of a nanofiber sheet, a nanofiber filtration film, a nanofiber grid, and combinations thereof, between substrates using a substrate assembly having a water-soluble layer in one embodiment. [Figure 8D] FIG. 1 illustrates the steps of an exemplary process for transferring nanofiber structures, including one or more of a nanofiber sheet, a nanofiber filtration film, a nanofiber grid, and combinations thereof, between substrates using a substrate assembly having a water-soluble layer in one embodiment. [Figure 8E] FIG. 1 illustrates the steps of an exemplary process for transferring nanofiber structures, including one or more of a nanofiber sheet, a nanofiber filtration film, a nanofiber grid, and combinations thereof, between substrates using a substrate assembly having a water-soluble layer in one embodiment. [Figure 8F]FIG. 1 illustrates the steps of an exemplary process for transferring nanofiber structures, including one or more of a nanofiber sheet, a nanofiber filtration film, a nanofiber grid, and combinations thereof, between substrates using a substrate assembly having a water-soluble layer in one embodiment. [Figure 8G] FIG. 1 illustrates the steps of an exemplary process for transferring nanofiber structures, including one or more of a nanofiber sheet, a nanofiber filtration film, a nanofiber grid, and combinations thereof, between substrates using a substrate assembly having a water-soluble layer in one embodiment. [Figure 8H] FIG. 1 illustrates the steps of an exemplary process for transferring nanofiber structures, including one or more of a nanofiber sheet, a nanofiber filtration film, a nanofiber grid, and combinations thereof, between substrates using a substrate assembly having a water-soluble layer in one embodiment. [Figure 8I] FIG. 1 illustrates the steps of an exemplary process for transferring nanofiber structures, including one or more of a nanofiber sheet, a nanofiber filtration film, a nanofiber grid, and combinations thereof, between substrates using a substrate assembly having a water-soluble layer in one embodiment. [Figure 8J] FIG. 1 illustrates the steps of an exemplary process for transferring nanofiber structures, including one or more of a nanofiber sheet, a nanofiber filtration film, a nanofiber grid, and combinations thereof, between substrates using a substrate assembly having a water-soluble layer in one embodiment. [Figure 8K] FIG. 1 illustrates the steps of an exemplary process for transferring nanofiber structures, including one or more of a nanofiber sheet, a nanofiber filtration film, a nanofiber grid, and combinations thereof, between substrates using a substrate assembly having a water-soluble layer in one embodiment. [Figure 9] FIG. 10 illustrates a method flow diagram for the exemplary method illustrated in FIGS. 8A-8K, according to one embodiment. [Figure 10]FIG. 10 illustrates a method flow diagram for the exemplary method illustrated in FIGS. 8A-8K, according to one embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] The above figures depict various embodiments of the present disclosure for illustrative purposes only. Numerous variations, configurations, and other embodiments will become apparent from the detailed discussion below. Furthermore, it will be understood that the above figures are not necessarily drawn to scale, nor are they intended to limit the described embodiments to the specific configurations shown in the figures. For example, while some figures generally show straight lines, right angles, and smooth surfaces, in a practical implementation of the disclosed technology, given real-world limitations of manufacturing processes, perfect straight lines and perfect right angles may not be met, and some features may have surface topographies or be otherwise non-smooth. In short, the above figures are presented merely to show example structures.
[0026] overview Nanofibers often have unique and interesting properties not present in similarly constructed bulk materials. However, due to the nanoscale dimensions of the individual nanofibers, some nanofiber-based materials can be difficult to handle. For example, carbon nanofiber sheets, while possessing interesting properties, are physically delicate and can tear, break, or be otherwise damaged by very little force during handling. Air currents generated by air handling equipment or operator breathing can damage nanofiber sheets. Due to this physically delicate nature, some development efforts have focused on improving the processing of nanofiber materials as well as exploring and applying their unique properties.
[0027] The techniques described herein include methods for transferring nanofibrous structures (e.g., nanofiber films; nanofiber sheets; stacks of nanofiber grids, nanofiber films, nanofiber sheets; and combinations thereof) between various substrates. The techniques described herein enable this transfer using liquid phase techniques that maintain the mechanical integrity of the nanofibrous structures and the purity of the nanofibrous structures. In other words, despite the delicate nature of nanofibrous structures, the techniques described herein do not damage or contaminate the nanofibrous structures.
[0028] Before describing these arrays and the methods for making them, a description of nanofibers, nanofiber filtration films, and nanofiber forests and nanofiber sheets will be provided.
[0029] Nanofiber Forest As used herein, the term "nanofiber" refers to fibers having a diameter of less than 1 μm. Although the embodiments herein are described as being primarily made from carbon nanotubes, it will be understood that other carbon allotropes, whether graphene, micron-scale or nanoscale graphite fibers and / or plates, and even nanoscale fibers of other compositions, such as boron nitride, can be processed using the techniques described below. As used herein, the terms "nanofiber" and "nanotube" are used interchangeably and include all single-walled nanotubes, few-walled nanotubes, and / or multi-walled nanotubes, in which the atoms are linked together to form a cylindrical structure. In some embodiments, the multi-walled nanotubes referred to herein have between 6 and 20 walls.
[0030] Nanotube dimensions can vary significantly depending on the production method used. For example, carbon nanotubes can have diameters from 0.4 nm to 100 nm, and lengths ranging from 10 μm to over 55.5 cm. Carbon nanotubes can also have very high aspect ratios (ratio of length to diameter) of about 132,000,000:1 or more. Given the wide range of possible dimensions, the properties of carbon nanotubes are highly adjustable or "tunable". While many interesting properties of carbon nanotubes have been identified, exploiting the properties of carbon nanotubes in practical applications requires scalable and controllable production methods that can maintain or improve the functionality of carbon nanotubes.
[0031] Due to their unique structure, nanotubes have specific mechanical, electrical, chemical, thermal and optical properties that make them suitable for specific applications. In particular, carbon nanotubes exhibit excellent electrical conductivity, high mechanical strength, good thermal stability, and are also hydrophobic. In addition to these properties, carbon nanotubes may also exhibit useful optical properties. For example, carbon nanotubes are used in light emitting diodes (LEDs) and photodetectors to emit or detect light at narrowly selected wavelengths. Carbon nanotubes may prove useful for photon transport and / or phonon transport.
[0032] According to various embodiments of the present disclosure, nanofibers (including, but not limited to, carbon nanotubes) can be arranged in a variety of configurations, including what is referred to herein as a "forest." As used herein, a "forest" of nanofibers or carbon nanotubes refers to an arrangement of nanofibers of approximately equal dimensions arranged substantially parallel to one another on a substrate. FIG. 1 illustrates an exemplary forest of nanofibers on a substrate. While the substrate can be any shape, in some embodiments, the substrate has a planar surface upon which the forest is constructed. As shown in FIG. 1, the nanofibers in the forest can be approximately the same height and / or diameter.
[0033] The nanofiber forests disclosed herein can be relatively dense. In particular, the density of the nanofiber forests disclosed herein can be at least 1 billion nanofibers / cm2. In some specific embodiments, the density of the nanofiber forests described herein can be 10 billion nanofibers / cm2 to 30 billion nanofibers / cm2. In other examples, the density of the nanofiber forests described herein can be 90 billion nanofibers / cm2. The forests may include regions of high or low density, and certain regions may be devoid of nanofibers. The nanofibers within the forest may also exhibit interfiber connectivity. For example, adjacent nanofibers within a nanofiber forest may be attracted to each other by van der Waals forces. Nevertheless, the density of nanofibers within the forest can be increased by applying the techniques described herein.
[0034] Methods for producing nanofiber forests are described, for example, in PCT Publication WO2007 / 015710, which is incorporated herein in its entirety.
[0035] A variety of methods can be used to produce nanofiber precursor forests. For example, in some embodiments, nanofibers can be grown in a high temperature furnace, as shown in the schematic diagram of FIG. 2. In some embodiments, a catalyst can be deposited on a substrate, placed in a reactor, and then exposed to a fuel compound fed into the reactor. The substrate can withstand temperatures above 800° C., or even above 1000° C., and can be an inert material. The substrate can comprise stainless steel or aluminum disposed on an underlying silicon (Si) wafer, although other ceramic substrates (e.g., alumina, zirconia, SiO2, glass ceramics) can be used in place of the Si wafer. In examples where the nanofibers of the precursor forest are carbon nanotubes, carbon-based compounds such as acetylene can be used as the fuel compound. After introduction into the reactor, the fuel compound(s) can begin to deposit on the catalyst and accumulate by growing upward from the substrate to form a forest of nanofibers. The reactor may also include a gas inlet through which fuel compound(s) and a carrier gas can be fed into the reactor, and a gas outlet through which consumed fuel compound and carrier gas can be released from the reactor. Examples of carrier gases include hydrogen, argon, and helium. These gases, especially hydrogen, may also be introduced into the reactor to promote the growth of a nanofiber forest. Additionally, dopants may be added to the gas stream to be incorporated into the nanofibers.
[0036] In the process used to produce a multi-layered nanofiber forest, one nanofiber forest is formed on a substrate, followed by the growth of a second nanofiber forest in contact with the first nanofiber forest. The multi-layered nanofiber forest can be formed by a number of suitable methods, such as by forming a first nanofiber forest on a substrate, depositing a catalyst on the first nanofiber forest, and then introducing additional fuel compounds into the reactor to promote the growth of the second nanofiber forest from the catalyst disposed on the first nanofiber forest. Depending on the growth methodology applied, the type of catalyst, and the location of the catalyst, the second nanofiber layer may be grown on top of the first nanofiber layer, or may be grown directly on the substrate, for example after reactivating the catalyst with hydrogen gas, and thus grown below the first nanofiber layer. Nevertheless, the second nanofiber forest can be arranged approximately end-to-end with the nanofibers of the first nanofiber forest, provided that there is an easily detectable interface between the first and second forests. The multi-layered nanofiber forest may include any number of forests. For example, a multi-layer precursor forest may include two, three, four, five or more forests.
[0037] Nanofiber Sheet In addition to being arranged in a forest configuration, the nanofibers of the present application may be arranged in a sheet configuration. As used herein, the term "nanofiber sheet," "nanotube sheet," or simply "sheet" refers to an arrangement of nanofibers in which the nanofibers are arranged end-to-end in a plane. As used herein, "nanofiber sheet" or simply "sheet" refers to a sheet of nanofibers aligned by a drawing process (described in PCT Publication No. WO 2007 / 015710, which is incorporated herein in its entirety) such that the longitudinal axes of the nanofibers of the sheet are parallel to the major surface of the sheet, rather than perpendicular to the major surface of the sheet (i.e., the sheet in its as-deposited form, often referred to as a "forest"). A diagram of an exemplary nanofiber sheet is shown in FIG. 3 with the three dimensions indicated. In some embodiments, the length and / or width of the sheet is greater than 100 times the thickness of the sheet. In some embodiments, the length, width, or both are greater than 103, 106, or 109 times the average thickness of the sheet. The thickness of the nanofiber sheet may be, for example, about 5 nm to 30 μm, and the length and width may be any size suitable for the intended application. In some embodiments, the length of the nanofiber sheet may be 1 cm to 10 meters, and the width may be 1 cm to 1 meter. These lengths are provided for illustrative purposes only. The length and width of the nanofiber sheet are constrained by the configuration of the manufacturing equipment, not by the physical or chemical properties of either the nanotubes, forests, or nanofiber sheets. For example, in a continuous process, sheets of any length may be manufactured. These sheets may be wound onto rolls as they are manufactured.
[0038] The axis along which the nanofibers are aligned end-to-end, as shown in Figure 3, is referred to as the nanofiber alignment direction. In some embodiments, the nanofiber alignment direction may be continuous throughout the nanofiber sheet. The nanofibers are not necessarily perfectly parallel to one another, and the nanofiber alignment direction is understood to be an average or general measure of the nanofiber alignment direction.
[0039] The nanofiber sheet can be constructed using any type of suitable process capable of producing the sheet. In some exemplary embodiments, the nanofiber sheet can be drawn from a nanofiber forest. An example of a nanofiber sheet being drawn from a nanofiber forest is shown in FIG. 4.
[0040] The nanofibers may be pulled laterally from the forest and then aligned end-to-end to form a nanofiber sheet, as shown in Figure 4. In embodiments where the nanofiber sheet is pulled from a nanofiber forest, the dimensions of the forest can be controlled to form a nanofiber sheet having specific dimensions. For example, the width of the nanofiber sheet can be approximately equal to the width of the nanofiber forest from which the sheet is pulled. Additionally, the length of the sheet can be controlled, for example, by terminating the drawing process once a desired sheet length is obtained.
[0041] Nanofiber sheets have many properties that can be utilized in a variety of applications. For example, nanofiber sheets can have tunable opacity, high mechanical strength and flexibility, thermal and electrical conductivity, and may also exhibit hydrophobicity. Given the high degree of alignment of the nanofibers within the sheet, the nanofiber sheets can be extremely thin. In some instances, the nanofiber sheets have a thickness of approximately 10 nm (measured within normal measurement tolerances), making the nanofiber sheets approximately two-dimensional. In other instances, the nanofiber sheets can have a thickness as high as 200 nm or 300 nm. Thus, the nanofiber sheets can be added to a component with minimal added thickness.
[0042] Similar to nanofiber forests, the nanofibers in a nanofiber sheet can be functionalized by treating agents that add chemical groups or elements to the surfaces of the nanofibers in the sheet, resulting in a different chemical activity than the nanofibers alone. Functionalization of the nanofiber sheet can be performed on nanofibers that have been previously functionalized or on nanofibers that have not been previously functionalized. Functionalization can be performed using any of the techniques described herein, including, but not limited to, CVD, as well as various doping techniques.
[0043] The nanofiber sheet as drawn from the forest of nanofibers can be of high purity, with greater than 90%, greater than 95%, or greater than 99% of the nanofiber sheet's weight being attributable to nanofibers. Similarly, the nanofiber sheet may contain greater than 90%, greater than 95%, greater than 99%, or greater than 99.9% carbon by weight.
[0044] Filtration Nanofiber Film Another planar form of constructed nanofibers is a "filter film" in which one or more of multi-walled nanotubes, few-walled nanotubes, and / or single-walled nanotubes are dispersed as a suspension in a solvent (the nanofibers are insoluble in the solvent). This dispersion can then be formed into a solid-state film of carbon nanotubes in which the carbon nanotubes are randomly oriented relative to each other in the plane of the film. In some cases, the dispersion is such that the majority of the nanotubes are individually suspended and not adsorbed to other nanotubes. The higher the degree of dispersion (e.g., fewer nanotubes adsorbed to each other in the solvent), the more uniform (i.e., uniform in thickness) the nanofiber film subsequently formed can be. This physical uniformity (which in some instances is further improved by laminating multiple filter films together) can also improve the uniformity of properties (e.g., transparency to radiation) throughout the film.
[0045] For purposes of clarity, multi-walled nanotubes are considered to have 4-20 concentric layers and a diameter between 4 nm and 100 nm, few-walled nanotubes are considered to have 2 or 3 concentric layers and a diameter between 2 nm and 6 nm, and single-walled carbon nanotubes are considered to have one layer and a tube diameter between 0.2 nm and 4 nm.
[0046] Each of these three different types of nanotubes can have different properties. In one example, few-walled carbon nanotubes and single-walled carbon nanotubes can be more easily dispersed in a solvent (i.e., the majority of the nanotubes are individually suspended and not adsorbed to other nanotubes) for subsequent formation into sheets of randomly oriented carbon nanotubes. This ability for the individual nanotubes to disperse uniformly in the solvent will in turn produce dimensionally uniform nanotube filtration films formed by removing the solvent from the suspended nanofibers.
[0047] The strength of the van der Waals attraction between nanofibers also differs between single / few-walled nanofibers and multi-layered nanofibers. Generally, single / few-walled nanofibers have a greater van der Waals attraction to each other than that observed in multi-layered nanofibers. This increased attraction between single / few-walled nanofibers can improve the ability of few / single-walled carbon nanotubes to adhere to each other to form coherent nanofiber structures, such as filtration films.
[0048] Sheets or films formed from single-walled and few-walled carbon nanotubes can conform to the topography of the underlying surface at smaller dimensions than sheets or films formed from multi-walled carbon nanotubes. In some instances, sheets or films formed from single-walled and / or few-walled carbon nanotubes can conform to topography of the underlying substrate as small as 10 nm, which is at least 50% smaller than the feature size that multi-walled carbon nanotube films can conform to. In some cases, multi-walled carbon nanotubes are more likely to aggregate together than single-walled / few-walled nanotubes, thereby producing a film with a non-uniform structure that is less likely to conform and / or adhere to the underlying surface.
[0049] The preparation of a filtration film may begin by preparing a solvent-free mixture of one or more of multi-walled nanotubes, few-walled nanotubes, and / or single-walled nanotubes in a desired ratio. This mixture of one or more different types of nanotubes may then be suspended in a solvent. In another example, separate suspensions of known concentrations of nanotubes in a solvent may be prepared. For example, separate suspensions of multi-walled carbon nanotubes, few-walled carbon nanotubes, and single-walled carbon nanotubes may be prepared. The suspensions may then be mixed in the desired ratios to reach the desired relative ratio of multi-walled nanotubes to few-walled / single-walled nanotubes in the combined suspension, and ultimately the final product filtration film.
[0050] The liquid phase of the suspension may be a polar compound, such as a polar protic compound or a polar aprotic compound. In some examples, the solvent used to prepare the nanotube suspension may include water, isopropyl alcohol (IPA), N-methyl-2-pyrrolidone (NMP), dimethyl sulfide (DMS), and combinations thereof. In some examples, a surfactant may be included to aid in uniform dispersion of the carbon nanofibers in the solvent. Examples of surfactants include, but are not limited to, sodium cholate, sodium dodecyl sulfate (SDS), and sodium dodecylbenzene sulfonate (SDBS). The weight percentage of the surfactant in the solvent may be anywhere from 0.1% to 10% by weight of the solvent. In one embodiment, a mixture of 50% by weight multi-walled carbon nanotubes and 50% by weight few-walled / single-walled carbon nanotubes may be prepared and suspended in water and SDS surfactant. Dispersion of the nanotubes in the solvent can include mechanical mixing (e.g., using a magnetic stir bar and stir plate), mechanical shaking, ultrasonic agitation (e.g., using an immersion ultrasonic probe), or other means.
[0051] As mentioned above, examples described herein can include nanofiber films that can be formed from one type of nanofiber (e.g., single-walled, few-walled, multi-walled) or a combination of these different types of nanofibers. Examples comprised of multiple types of nanofibers may be described as "composite films" by combining or blending different nanofiber types. In some examples herein, the median length of the multi-walled carbon nanotubes can be about 300 μm (±10%). As will be understood with reference to the following description, to improve the mechanical stability of filtration films that also include generally shorter (e.g., 0.5 μm to 30 μm) single-walled and / or few-walled carbon nanotubes, the filtration films may include multi-walled carbon nanotubes that are at least 250 μm in length. Films formed solely from either longer multi-walled nanotubes or shorter few-walled / single-walled carbon nanotubes are generally not as durable (i.e., resistant to mechanical failure, such as cracking or crumbling) as films that include a mixture of multi-walled nanotubes and few-walled / single-walled nanotubes.
[0052] The suspension is passed through a filter that is permeable to the solvent but impermeable to the nanofibers. One example of an exemplary filter is a common laboratory paper filter. Other types of filters can also be used as long as they are permeable to the solvent and impermeable to the nanofibers.
[0053] The solvent is then separated from the suspended nanofibers by passing it through the filter, thus leaving a filtration film on the top surface of the filter. In some instances, the solvent can be separated from the nanofibers (i.e., the solid phase component of the suspension) by simply passing it through the filter under gravity. In other instances, the solvent can be forced through the filter by selectively applying negative pressure (i.e., vacuum) to the side of the filter opposite the suspension, or positive pressure to the side of the filter opposite the suspension. In some instances, heat can be applied to the filtration film after separation using the filter to facilitate removal of the solvent by drying.
[0054] The filtration film can be removed from the filter by immersion in deionized water. Because the nanofiber film is hydrophobic and simply rests on the filter (not bonded), the filtration film will naturally lift off the filter and float on the water surface. A frame or other substrate can then be used to lift the film off the water surface, thus placing the filtration film on the frame or substrate. If necessary, the surface tension of the water (or other solvent) can be altered by adding a surfactant or other solvent. The filtration film can then be dried (e.g., using a low humidity environment, heat, vacuum). This process can be repeated to form different films of mixtures of different compositions of multi-layer, few-layer, and / or single-layer nanofibers, optionally.
[0055] After removal, the filtration film (or stack of filtration films) may be dried by exposure to a low relative humidity environment, heat, or other drying techniques.
[0056] FIG. 5 is a schematic diagram of a composite nanotube filtration film 500 according to one embodiment of the present disclosure. As shown, the composite nanotube filtration film 500 includes single-walled / few-walled nanotubes 504 interdispersed with multi-walled carbon nanotubes 508. In this exemplary film 500, the single-walled / few-walled carbon nanotubes 504 can provide at least two beneficial effects to the overall structure of the film 500. For example, the single-walled / few-walled carbon nanotubes 504 can increase the number of indirect bonds between adjacent multi-walled carbon nanotubes 508 by filling the gaps between the adjacent multi-walled carbon nanotubes 508. The interconnections between the short and long nanofibers can improve the transfer and distribution of forces applied to the film, thus improving durability. In a second example of a beneficial effect, the single-walled / few-walled carbon nanotubes 504 can reduce the median and / or average size of the gaps between adjacent and / or overlapping multi-walled carbon nanotubes 508, which may be advantageous in some embodiments. Furthermore, too many longer multi-walled carbon nanotubes can agglomerate when dispersed in the solvent, which can lead to non-uniform films. Shorter nanotubes disperse more easily in the solvent and are therefore more likely to form dimensionally uniform films with a uniform density of nanotubes per unit volume.
[0057] FIG. 6 is an electron microscope image of a filtration film containing a mixture of multi-walled and few-walled and / or single-walled nanotubes prepared according to the techniques described above.
[0058] Properties of nanofiber filtration films Filtering films, especially those made with single-walled and / or few-walled carbon nanotubes, generally have greater transparency to radiation at some wavelengths. In some instances, the transmission of incident radiation can be as high as 90% or 95%. In some cases, this transmission is significantly higher than that of drawn sheets of multi-walled carbon nanotubes (such as those drawn from carbon nanotube forests, described below). Without wishing to be bound by theory, it is believed that the orientation of the nanotubes in the drawn sheets increases the scattering of radiation compared to filtering films. In part, the greater transparency of filtering films (including their randomly oriented nanotubes) has led to interest in forming transparent filters and pellicles from filtering carbon nanotube films for various applications.
[0059] Despite the above advantages of single-walled and few-walled carbon nanotubes, multi-walled carbon nanotubes also have advantages that are not necessarily observed to the same extent in nanotube structures formed from single-walled or few-walled nanotubes. For example, structures formed from multi-walled carbon nanotubes are generally observed to have higher emissivity than structures formed from few-walled / single-walled carbon nanotubes. Without wishing to be bound by theory, it is believed that the higher number of layers and larger diameter of multi-walled carbon nanotubes are responsible for the increased emissivity. For example, the thermal emissivity of multi-walled carbon nanotube structures (e.g., nanotube forests, nanotube sheets) is greater than that of nanotube structures formed from few-walled / single-walled nanotubes. In one comparative example, the emissivity of nanofiber structures including multi-walled carbon nanotubes is approximately 0.275 (±15%), while the emissivity of nanofiber structures including single-walled carbon nanotubes may be significantly lower, at 0.05 (±15%). High emissivity is particularly advantageous in technological applications where processes in the application may cause heating within the nanofibrous structure, but conductive or convective cooling mechanisms of the nanofibrous structure are limited or not technically feasible.
[0060] For example, nanofiber structures transparent to certain wavelengths of radiation (e.g., extreme ultraviolet or "EUV" in the range of 10 nm to 124 nm) are expected to be used as filters (also called "pellicles") in EUV lithography devices. Pellicles can act as particle filters that prevent foreign particles from settling on the surface of the material being patterned and / or on the surface of the lithography mask used to pattern the photoactive surface. This reduces the rate of defects introduced during lithography, which in turn increases the yield of fabrication of patterned devices.
[0061] Despite their high transparency in the EUV radiation wavelength range, challenges remain in the adoption of nanofiber EUV pellicles. For example, cooling of nanofiber pellicles can be important to prevent overheating of the pellicle due to absorption of EUV energy during lithographic patterning. Increased pellicle temperature can compromise the integrity of the nanofiber structure. However, considering that EUV lithography is performed in a vacuum and the pellicle is most often suspended (attached to a frame at its peripheral edges), the opportunity for convective and / or conductive cooling of the nanofiber structure in this environment is low. Thus, thermal radiation is the primary mechanism for cooling of nanofiber pellicles used in EUV applications.
[0062] Multi-walled carbon nanotube structures generally have higher emissivity, which addresses the cooling problem of EUV pellicles, but multi-walled carbon nanotubes, when aligned in drawn sheets, are also less transparent than the randomly oriented single / few-walled carbon nanofibers in filtration films. More transparent (but lower emissivity) few / single-walled nanofiber films are often too mechanically delicate to be used as pellicles. In some cases, films and sheets made from few / single-walled nanofibers are fragile due to the relatively short length of their nanofibers (e.g., less than 100 μm) and will collapse when subjected to pressure cycles (e.g., ±1-2 atmospheres of pressure change (from atmospheric pressure to vacuum)) commonly used in EUV lithography machines.
[0063] In another set of embodiments, the filtration films described herein can form transparent conductive films (TCFs). To this end, the filtration films can exhibit low electrical resistance and high optical transparency. TCFs can comprise single-walled, double-walled, or multi-walled filtration films. These filtration films can be single-walled CNTs only, few-walled CNTs only, multi-walled CNTs only, or combinations thereof. For example, the weight ratio of single-walled / few-walled nanotubes to multi-walled nanotubes in the TFT can be greater than 1:1, greater than 5:1, greater than 10:1, greater than 50:1, greater than 100:1, less than 1:1, less than 1:2, less than 1:5, less than 1:10, less than 1:20, less than 1:50, or less than 1:100. In various embodiments, the TCFs may be constructed to have an electrical resistance of less than 10,000 Ω / sq, less than 1,000 Ω / sq, less than 100 Ω / sq, less than 10 Ω / sq, or less than 1.0 Ω / sq. In the same or different embodiments, the transparency of the film in the visible light range may be greater than 60%, greater than 75%, greater than 90%, greater than 95%, greater than 98%, or greater than 99%.
[0064] These low resistance levels and high transparency can be achieved with or without coatings on the nanotubes such as conductive silver. In some embodiments, this result is achieved without the use of indium. The filtration films may be on one or more substrates or may be substrate-free. The films can conform to many shapes and may be adhered to or used in conjunction with surfaces such as optical sensors, lenses, and windows.
[0065] Treatment of nanofiber films with soluble substrates In some cases, the use of a substrate having a soluble layer on an exposed surface of the substrate can facilitate the processing of nanofibrous structures, particularly nanofibrous structures with multiple layers. For example, nanofibrous structures including one or more of nanofibrous sheets, nanofibrous grids, and / or nanofibrous films can be fragile. The use of a water-soluble layer to release the nanofibrous structures from the substrate can improve the convenience of removing these delicate structures from one substrate and, optionally, placing them on a final substrate.
[0066] 7(A)-(C) and 8A-8K show various stages of an exemplary process for using a substrate with a soluble layer to facilitate the transfer of a nanofiber substrate. The following examples are primarily described with respect to a water-soluble layer of NaCl, but it will be understood that other water-soluble compositions can be used, including other inorganic salts such as CaCl and KBr, starch, or even other combinations of non-aqueous solvents and corresponding soluble compositions (e.g., polystyrene and toluene). For reasons explained below, the soluble layer can also be selected for the transparency of the soluble layer to some wavelengths of radiation, particularly those used by lasers. In this way, when a laser is used to cut a nanofiber structure on a water-soluble layer, the laser does not heat or degrade the underlying water-soluble layer. The advantage of water and NaCl in particular is that both can be removed from the nanofiber structure, and NaCl is transparent to some wavelengths of laser infrared radiation used to cut the nanofiber structure. In other cases, for example, it may be desirable to infiltrate the nanofiber structure with a polymer, and therefore using a polymer layer on the substrate with a corresponding organic solvent may be a preferred combination.
[0067] Turning first to FIG. 7(A), the nanofiber structure 704 may be disposed on a substrate 708. In one example, the nanofiber structure 704 may be a filtration nanofiber film, and the substrate 708 may be a glass substrate, a polymer substrate, or a filter paper. In some examples, the substrate 708 need not even be planar, but may instead have a convex or concave shape. This is because it is possible to remove nanofiber structures from substrates with these topographies using techniques described below. As shown in FIG. 7(B), the nanofiber film 704 and substrate 708 may be immersed in a container 712 of water (indicated by arrow "A") or below the water surface 716 (indicated by arrow "B"). As described above, the portion of the filtration nanofiber film 704B in contact with the water floats above the water surface 716. While a portion of the filtration nanofiber film 704B is above the water surface, that portion remains attached to the substrate 708. However, once that portion comes into contact with the water surface 716, it also peels off (as indicated by arrow "C") from the substrate 708. Once the filtration film 704 is completely peeled off from the substrate 708, it will float on the water surface 716, as shown in Figure 7(C).
[0068] Turning now to Figure 8A, the nanofiber structure 704 may be lifted out of the water using a frame 804. In Figure 8A, the frame 804 is shown as a dashed line to indicate its location below the nanofiber structure 704. In some examples, the frame may be a wire frame with an open center, thus keeping the corresponding portion of the nanofiber film 704 free-standing and further facilitating the removal of the nanofiber structure from the frame 804.
[0069] 8B illustrates a nanofiber grid 808 that can be fabricated according to the methods described in U.S. Patent Application Serial No. 16 / 242,086 (corresponding to U.S. Patent Publication No. US2019 / 0218099), which is incorporated herein by reference in its entirety. As shown in a schematic diagram, the nanofiber grid 808 comprises laterally arranged nanofiber bundles separated by gaps defined between the bundles. The nanofiber grid 808 is shown comprising orthogonal vertical nanofiber bundles 810A and horizontal nanofiber bundles 810B. It will be understood that this depiction is for convenience of illustration only, and that the nanofiber bundles 810A, 810B may be oriented in any direction and with respect to each other in a uniform or random manner.
[0070] Turning to FIGS. 8C and 8D, the nanofiber grid 808 may be disposed on a substrate assembly 812, which may include a substrate 820 and a soluble layer 816 on the substrate 820. Examples of the substrate 820 include, but are not limited to, glass (e.g., borosilicate glass), silica (SiO2), silicon (Si) wafers, polymer sheets (e.g., polycarbonate, polyethylene), and steel, among others. The soluble layer 816, as shown above, may be any of a number of soluble materials. In this example, the soluble layer 816 is a layer of NaCl between 25 microns (μm) and 100 μm thick. In this example, the soluble layer 816 may be sprayed onto the substrate 820 as a saturated solution of water and NaCl. The substrate 820 may be heated or preheated to facilitate evaporation of the water from the sprayed solution and the formation of the soluble layer 816. It will be appreciated that other deposition techniques can be used for this combination of solute (used to form soluble layer 816) and solvent, as well as other techniques. For example, drip casting and / or spin casting may be used instead of (or in addition to) spray casting in both the case of the NaCl / water solution and the polymer / organic solvent solution. Typically, soluble layer 816 will be 10 μm to 200 μm thick. This thickness can be individualized based on the concentration of solute in the solvent in the solution applied by drip casting, spin casting, or spray casting, as well as the amount of solution applied to substrate 820.
[0071] As shown in Figures 8E and 8E', the filtration film 704 may be disposed over a nanofiber grid 808 on a substrate assembly 812. The stack of filtration film 704 on nanofiber grid 808 forms a nanofiber structure assembly 824. As noted above, nanofiber structure assembly 824 may be formed from any combination of any number of nanofiber sheets, nanofiber filtration films, and nanofiber grids. In the example shown, it will be appreciated that the nanofiber film 704 may hang down between adjacent nanofiber bundles 810A, 810B (collectively and generally 810) of the nanofiber grid 808. This hanging down is shown in Figure 8E' as a protruding portion.
[0072] Optionally, the nanofiber structure assembly 824 on the substrate assembly 812 may be cut or shaped into any pattern, shape, or combination of shapes. FIG. 8F shows cutting the nanofiber structure assembly 824 with a laser beam 836 generated by a laser diode device 832. Other cutting systems include electrical discharge devices (corona or electric arc (e.g., using "EDM")) and thermal cutting devices. In the example of FIG. 8F, the combination of the NaCl soluble layer 816 with an infrared (IR) laser beam 836 is useful at least because NaCl is transparent to IR radiation. Thus, the nanofiber structure assembly 824 can be cut with the laser beam 836 without heating, burning, or otherwise degrading the soluble layer 816. Thus, unintended thermal damage and / or contamination of the nanofiber structure assembly 824 is avoided.
[0073] 8G illustrates exemplary shapes into which the nanofibrous structure assembly 824 has been cut. As shown in this figure for purposes of illustration only, the nanofibrous structure assembly 824 has been cut into an ellipse 840, a rectangle 844, and an irregular shape 848. It will be appreciated that the nanofibrous structure assembly 824 may be cut into any shape, including regular polygons, irregular polygons, annulus shapes, rings, spirals, among others. The portion(s) of the nanofibrous structure assembly 824 that is not of the desired shape may be removed, thus exposing the soluble layer 816.
[0074] In some instances, nanofiber structure assembly 824 can be supplemented by placing a nanofiber sheet, or in this case, nanofiber film 852, over features 840, 844, 848, thus forming a second nanofiber structure assembly 856, a top view of which is shown in Figure 8H, and a cross-sectional view taken at the location shown in Figure 8H is shown in Figure 81.
[0075] 7(A)-(C) and described above, second nanofibrous structure assembly 856 can then be removed from substrate 820 by placing second nanofibrous structure assembly 856 in water 860. In some instances, second nanofibrous structure assembly 856 can be allowed to remain on water 860 for a period of time (e.g., 5 minutes, 30 minutes, 60 minutes, 120 minutes) such that any residual salt (or other soluble layer material) is removed from second nanofibrous structure assembly 856.
[0076] The second nanofiber structure 856 may then be removed from the water using a frame or final substrate 864 and optionally cut into one or more of the shapes 840, 844, 848 shown above. The final substrate 864 may comprise any crystalline or amorphous material (e.g., polymer, borosilicate glass, silicon, acrylic, ITO, zinc sulfide) and may be rigid or flexible. The topography of the final substrate may be flat or rounded. The assembly may be dried using heat and / or vacuum to remove residual solvent (e.g., water).
[0077] 9 and 10 show flow diagrams of exemplary methods corresponding to embodiments of the processes described above.
[0078] Further considerations The above description of embodiments of the present disclosure has been presented for purposes of illustration and is not intended to be exhaustive or to limit the scope of the claims to the precise form disclosed. Those skilled in the relevant art will recognize that many modifications and variations are possible in light of the above disclosure.
[0079] The language used in this specification has been selected primarily for ease of reading and instructional purposes, and may not have been selected to describe or limit the subject matter of the present invention. Accordingly, the scope of the disclosure is intended to be limited not by this detailed description, but by any claims filed based on this specification upon filing. Accordingly, the disclosure of the present embodiments is intended to illustrate, but not limit, the scope of the invention, which is set forth in the following claims.
Claims
1. A nanofiber film assembly comprising a nanofiber structure and a substrate assembly, the substrate assembly comprising a substrate and a soluble inorganic salt layer; The soluble inorganic salt layer is provided between the nanofiber structure and the substrate, the soluble inorganic salt layer is configured to be dissolvable when the nanofiber film assembly is immersed in a solvent, and dissolution of the soluble inorganic salt layer detaches the nanofiber structure from the substrate and causes the nanofiber structure to float on the surface of the solvent. Nanofiber film assembly.
2. 10. The nanofiber film assembly of claim 1, wherein the nanofiber structure has an electrical resistance of less than 10,000 ohms / square.
3. 10. The nanofiber film assembly of claim 1, wherein the nanofiber structure is transparent to greater than 60% of visible light.
4. 10. The nanofiber film assembly of claim 1, wherein the soluble inorganic salt layer comprises at least one of sodium chloride, calcium chloride, and potassium bromide.
5. 10. The nanofiber film assembly of claim 1, wherein the nanofiber structure is configured to be cut using at least one of a laser beam and an electric discharge device without causing damage to the soluble inorganic salt layer.
6. the nanofiber structure is a nanofiber sheet, a nanofiber film, a nanofiber grid, or a combination thereof; The nanofiber sheet is a nanofiber sheet extracted from a nanofiber forest, the nanofiber film is a nanofiber filtration film; 10. The nanofiber film assembly of claim 1, wherein the nanofiber grid comprises at least one layer of nanofiber bundles, the nanofiber bundles being separated by gaps and laterally disposed.
7. 10. The nanofiber film assembly of claim 1, wherein the nanofiber structure comprises at least two stacked carbon nanofiber layers.
8. each of the nanofiber layers comprises at least one of a carbon nanofiber drawn sheet, a carbon nanofiber filtration film, and a carbon nanofiber grid; The carbon nanofiber grid includes at least one layer of a plurality of nanofiber bundles; 8. The nanofiber film assembly of claim 7, wherein the plurality of nanofiber bundles are separated and laterally disposed by gaps.
9. 10. The nanofiber film assembly of claim 8, wherein the carbon nanofiber grid is disposed directly on the surface of the substrate.
10. a first layer of the at least two stacked carbon nanofiber layers is the carbon nanofiber-extracted sheet or the carbon nanofiber filtration film; a second layer of the at least two stacked carbon nanofiber layers is the carbon nanofiber grid; 10. The nanofiber film assembly of claim 9, wherein portions of the first layer between adjacent nanofiber bundles of the carbon nanofiber grid hang down.
11. Obtaining a substrate; providing a soluble inorganic salt layer on a surface of the substrate to form a substrate assembly; and disposing a nanofiber structure on the exposed surface of the soluble inorganic salt layer to form a nanofiber film assembly, comprising: immersing the nanofiber film assembly in a solvent to dissolve the soluble inorganic salt layer in the solvent, peeling off the nanofiber structure, and floating the nanofiber structure on the surface of the solvent; method.
12. attaching the peripheral edges of the nanofiber structure suspended on the surface of the solvent to a frame having an open center; The method of claim 11 , further comprising withdrawing the frame and the nanofiber structure from the surface of the solvent.
13. 12. The method of claim 11, wherein the soluble inorganic salt layer comprises sodium chloride, calcium chloride, or potassium bromide and the solvent is water.
14. The method of claim 11 , further comprising cutting the nanofibrous structure with an infrared laser prior to immersing the nanofibrous structure in a solvent.
15. The method of claim 11 , wherein the substrate comprises one or more selected from the group consisting of glass, silica, silicon, polymer, filter paper, and steel.
16. The method of claim 11, wherein the soluble inorganic salt layer has a thickness of 10 μm to 200 μm.
17. the nanofiber structure is a nanofiber sheet, a nanofiber film, a nanofiber grid, or a combination thereof; The nanofiber sheet is a nanofiber sheet extracted from a nanofiber forest, the nanofiber film is a nanofiber filtration film; The method of claim 11 , wherein the nanofiber grid comprises at least one layer of nanofiber bundles, the nanofiber bundles being separated by gaps and laterally disposed.
18. The method of claim 11 , wherein the nanofiber structure comprises at least two carbon nanofiber layers.
19. 20. The method of claim 18, wherein each of the carbon nanofiber layers comprises at least one of a carbon nanofiber sheet, a carbon nanofiber filtration film, and a carbon nanofiber grid.
20. Immersing a portion of the nanofiber structure in the solvent; dissolving a portion of the soluble inorganic salt layer; The method of claim 11 , further comprising exfoliating a portion of the nanofibrous structure and floating it on the surface of the solvent.
Citation Information
Patent Citations
Method for producing carbon nanotube dispersion
JP2007063051A
Carbon nanotube self-supporting film, its production method, constituent body having carbon nanotube film, and method for production thereof
JP2007182342A
Method for production of substrate with carbon nanotube
JP2008273785A
Manufacturing and application of nanofiber ribbons and sheets, as well as twisted and untwisted nanofiber yarns.
JP2008523254A
Nanofiber laminate sheet
JP2012012317A